A Monocarbonyl Curcuminoid Derivative Inhibits the Activity of Human Glutathione Transferase A4-4 and Chemosensitizes Glioblastoma Cells to Temozolomide - Steliana Tsouri; Evanthia Tselo; Georgios E. Premetis; Veronika Furlan; Panagiota D. Pantiora; Barbara Mavroidi; Dimitris Matiadis; Maria Pelecanou; Anastassios C. Papageorgiou; Urban Bren; Marina Sagnou; Nikolaos E. Labrou (MDPI AG, 2024)
Human glutathione transferase A4-4 (hGSTA4-4) displays high catalytic efficiency towards 4-hydroxyalkenals and other cytotoxic and mutagenic products of radical reactions and lipid peroxidation. Its role as a target for the chemosensitization of cancer cells has not been investigated so far. In this study, the inhibitory potency of twelve selected natural products and ten monocarbonyl curcumin derivatives against hGSTA4-4 was studied. Among natural products, ellagic acid turned out to be the strongest inhibitor with an IC50 value of 0.44 ± 0.01 μM. Kinetic analysis using glutathione (GSH) and 1-chloro-2,4-dinitrobenzene (CDNB) as variable substrates showed that ellagic acid behaved as a competitive inhibitor towards both GSH and CDNB, with Ki values of 0.39 ± 0.02 and 0.63 ± 0.03 μM, respectively. Among the curcumin derivatives studied, three proved to be the most potent inhibitors, in the order DM151 > DM101 > DM100, with IC50 values of 2.4 ± 0.1 μM, 12.7 ± 1.1 μΜ and 16.9 ± 0.4 μΜ, respectively. Further kinetic inhibition analysis of the most active derivative, DM151, demonstrated that this compound is a mixed inhibitor towards CDNB with inhibition constants of Ki = 4.1 ± 0.5 μM and Ki' = 0.536 ± 0.034 μM, while it is a competitive inhibitor towards GSH with a Ki = 0.98 ± 0.11 μM. Molecular docking studies were performed to interpret the differences in binding of ellagic acid and curcumin derivatives to hGSTA4-4. The in silico measured docking scores were consistent with the obtained experimental data. Hydrogen bonds appear to be the main contributors to the specific binding of monocarbonyl curcumin derivatives, while π-π stacking interactions play a key role in the enzyme-ellagic acid interaction. In vitro cytotoxicity assessment of the worst (DM148) and the best (DM151) inhibitors was performed against glioblastoma cell lines U-251 MG and U-87 MG. The results revealed that DM151 displays considerably higher cytotoxicity against both glioblastoma cell lines, while the glioblastoma cytotoxicity of DM148 was very limited. Furthermore, low and non-toxic doses of DM151 sensitized U-251 MG cells to the first-line glioblastoma chemotherapeutic temozolomide (TMZ), allowing us to propose for the first time that hGSTA4-4 inhibitors may be attractive therapeutic partners for TMZ to optimize its clinical effect in glioblastoma chemotherapy.